Lógicas dominantes en la formulación de políticas y organización de servicios que inciden en el acceso a la rehabilitación integral (2016)
Introduction: The health sector reform in Colombia, generated inequities in access to services, including rehabilitation; poor identification of population needs and low sectorial response to their problems. Metodology: An exploratory, descriptive-interpretative qualitative study was carried out. Individual semi-structured interviews and focus group were conducted to policy makers, providers, rehabilitation professionals, professors, social organizations, persons with disabilities and caregivers. Results: The absence of a rights approach, targeting and the model of health insurance, as dominant logics policy stands. There is a reductionist view of rehabilitation and services organization models with low response to the needs of people with disabilities. Conclusion: The need to reconceptualize access to services arises; rehabilitation is claimed as a right that demands redesign of services and organization models.